2013
DOI: 10.1590/0074-0276130457
|View full text |Cite
|
Sign up to set email alerts
|

COI barcode versus morphological identification of Culex ( Culex ) (Diptera: Culicidae) species: a case study using samples from Argentina and Brazil

Abstract: Sequences of the cytochrome c oxidase subunit I (COI) mitochondrial gene from adults of 22 Culex ( Culex ) species from Argentina and Brazil were employed to assess species identification and to test the usefulness of COI for barcoding using the best close match (BCM) algorithm. A pairwise Kimura two-parameter distance matrix including the mean intra and interspecific distances for 71 COI barcode sequences was constructed. Of the 12 COI lineages recovered in the Neighbour-joining topology, five confirmed recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 64 publications
6
85
0
4
Order By: Relevance
“…Indeed, morphological and molecular comparisons of the COI sequence do appear congruent in studies across genus levels, as attested by morphological species' studies on mosquito diversity from Argentina (Laurito et al 2013), Australia (Batovska et al 2016), China (Wang et al 2012), India (Kumar et al 2007), Singapore (Chan et al 2014), Italy (Talbalaghi andShaikevich, 2011), Iran (Azari-Hamidian et al 2009) and Pakistan (Ashfaq et al 2014). This latter study from Pakistan reveals intraspecific divergences at a maximum of 2.4% from over 1600 individuals from 24 taxa -a result in line with the original Canadian work.…”
Section: T H E M T D N a C O I B A R C O D Ementioning
confidence: 84%
“…Indeed, morphological and molecular comparisons of the COI sequence do appear congruent in studies across genus levels, as attested by morphological species' studies on mosquito diversity from Argentina (Laurito et al 2013), Australia (Batovska et al 2016), China (Wang et al 2012), India (Kumar et al 2007), Singapore (Chan et al 2014), Italy (Talbalaghi andShaikevich, 2011), Iran (Azari-Hamidian et al 2009) and Pakistan (Ashfaq et al 2014). This latter study from Pakistan reveals intraspecific divergences at a maximum of 2.4% from over 1600 individuals from 24 taxa -a result in line with the original Canadian work.…”
Section: T H E M T D N a C O I B A R C O D Ementioning
confidence: 84%
“…In our analyses, COI barcode was even able to differentiate several mosquito species that were difficult to distinguish morphologically. However, empirical evidence has shown that COI-based barcoding is not successful all the time [21][22][23]. Firstly, the limited availability of sequences to be used as references for comparison has restricted its usage on species identification.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proven that COI gene is an efficient and useful barcode for the identification of metazoans, including mosquitoes [21][22][23][24][25][26]. However, COI barcode may not be universally applicable to identify all animal species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ease to amplify and sequence this mitochondrial fragment is one of the reasons it has become so popular (Fomer et al 1994). Several authors have used the mitochondrial DNA, COI sequences, to study the cosmopolitan genus Culex, in search of an efficient tool that can readily confirm confusing taxonomical issues, a well-documented limitation for the study of this particular taxon (Cywinska et al 2006;Kumar et al 2007;Wang et al, 2012;Laurito et al 2013). …”
Section: Introductionmentioning
confidence: 99%